Lipoprotein particles and coronary artery calcium in middle-aged US-White and Japanese men. Issue 2 (29th December 2019) - Mahajan, Hemant; Zaid, Maryam; Mackey, Rachel; Kadota, Aya; Vishnu, Abhishek; Fujiyoshi, Akira; Vasudha, Ahuja; Hisamatsu, Takashi; Evans, Rhobert; Okamura, Tomonori; Miura, Katsuyuki; Kuller, Lewis; et al.
Abstract : Objective: This cross-sectional study examined whether contrasting distributions of nuclear magnetic resonance (NMR)-measured lipoproteins contribute to differences in the prevalence of subclinical atherosclerosis measured using coronary artery calcium (CAC) between the two groups of middle-aged males: the US-residing Caucasian (US-White) and Japan-residing Japanese (Japanese). Methods: In a population-based study of 570 randomly selected asymptomatic men aged 40–49 years (270 US-White and 300 Japanese), we examined the relationship between race/ethnicity, NMR-measured lipoproteins and CAC (measured by Electron Beam CT and quantified using the Agatston method) using multivariable robust Poisson regression adjusting for traditional and novel risk factors for coronary heart disease (CHD). Results: The US-White compared with the Japanese had significantly different NMR-measured lipoprotein particle distributions. The US-White had a significantly higher prevalence of CAC≥10 (CAC-prevalence) compared with the Japanese adjusting for CHD risk factors (prevalence ratio (PR)=2.10; 95% CI=1.24 to 3.48), and this difference was partially attenuated ( 18%) with further adjustment for lipoprotein levels (PR=1.73; 95% CI=1.02 to 3.08). There was no reclassification improvement with further addition of lipoproteins particle concentrations/size to a model that already included traditionally measured lipids (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglycerides), cardiovascular risk factors, and inflammatory markers (net reclassification improvement index=−2% to 3%). Conclusions: Variations in the distribution of NMR-measured lipoprotein particles partially accounted for the difference in the CAC-prevalence between middle-aged US-White and Japanese men.